2018
DOI: 10.1186/s12933-017-0646-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 6-month treatment with the glucagon like peptide-1 analogue liraglutide on arterial stiffness, left ventricular myocardial deformation and oxidative stress in subjects with newly diagnosed type 2 diabetes

Abstract: BackgroundIncretin-based therapies are used in the treatment of type 2 diabetes mellitus (T2DM) and obesity. We investigated the changes in arterial stiffness and left ventricular (LV) myocardial deformation after 6-month treatment with the GLP-1 analogue liraglutide in subjects with newly diagnosed T2DM.MethodsWe randomized 60 patients with newly diagnosed and treatment-naive T2DM to receive either liraglutide (n = 30) or metformin (n = 30) for 6 months. We measured at baseline and after 6-month treatment: (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
107
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(116 citation statements)
references
References 52 publications
8
107
1
Order By: Relevance
“…in vitro studies suggest these agents may have effects on adhesion molecules and endothelial function that may inhibit atherosclerosis and thrombosis . A randomized trial in patients with newly diagnosed and treatment‐naïve type 2 diabetes found that six months of liraglutide treatment improved arterial stiffness and left ventricular myocardial strain, and reduced N‐terminal pro b‐type natriuretic peptide independently of weight loss by reducing oxidative stress . A meta‐analysis in patients with type 2 diabetes has also indicated that GLP‐1‐based therapy is associated with an increase in flow‐mediated dilation, reductions in atherosclerotic markers such as C‐reactive protein, plasminogen activator inhibitor‐1 and B‐type natriuretic peptide, as well as reductions in LDL cholesterol and triglycerides …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in vitro studies suggest these agents may have effects on adhesion molecules and endothelial function that may inhibit atherosclerosis and thrombosis . A randomized trial in patients with newly diagnosed and treatment‐naïve type 2 diabetes found that six months of liraglutide treatment improved arterial stiffness and left ventricular myocardial strain, and reduced N‐terminal pro b‐type natriuretic peptide independently of weight loss by reducing oxidative stress . A meta‐analysis in patients with type 2 diabetes has also indicated that GLP‐1‐based therapy is associated with an increase in flow‐mediated dilation, reductions in atherosclerotic markers such as C‐reactive protein, plasminogen activator inhibitor‐1 and B‐type natriuretic peptide, as well as reductions in LDL cholesterol and triglycerides …”
Section: Discussionmentioning
confidence: 99%
“…The accrual of more events in SUSTAIN 6 allowed that trial to identify a significantly lower risk of the primary outcome (albeit not pre‐specified before trial initiation) of three‐point MACE among patients treated with s.c. semaglutide compared with placebo ( P = 0.02 for superiority of s.c. semaglutide) . It has been suggested that trial duration is a factor in being able to demonstrate CV risk reductions in diabetes CV outcomes trials . Nevertheless, a relatively short trial duration was used for PIONEER 6 to allow the CV safety of oral semaglutide to be determined early in the development programme and because the CV safety of semaglutide as a s.c. formulation had already been demonstrated in SUSTAIN 6; however, due to the short duration and expected accrual of fewer events than SUSTAIN 6, a statistically significant CV risk reduction with oral semaglutide versus placebo may be less likely.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the work of Lambadiari and colleagues in patients with DM using liraglutide showed that 6 months of treatment resulted in significant improvement of endothelial function, arterial stiffness, left ventricular strain with reduction of the NT‐proBNP marker, and oxidative stress. As previously discussed, treatment of type 2 DM with new oral hypoglycemic agents such as sodium‐glucose co‐transporter 2 inhibitors showed promising results with significant reduction in BP, weight, endothelial dysfunction, arterial stiffness, and microalbuminuria in patients with hypertension and those with DM …”
Section: Discussionmentioning
confidence: 99%
“…A dipeptidyl peptidase 4 (DPP-4) inhibitor either improved [23], had no effect [26], or worsened [27] endothelial function but did not affect cardiovascular events [28,29]. In another study, GLP-1 analog treatment enhanced [30,31] or had no effect on [32] endothelial function. In patients with type 2 diabetes, liraglutide, a GLP-1 analog, was successful in preventing nonfatal myocardial infarction or stroke, along with death from cardiovascular causes [33].…”
Section: Discussionmentioning
confidence: 99%